CTAO LST–1 observations of magnetar SGR 1935+2154: Deep limits on sub-second bursts and persistent tera-electronvolt emission - Abe, K.; Abe, S.; Abhishek, A.; Acero, F.; Aguasca-Cabot, A.; Agudo, I.; Alispach, C.; Ambrosino, D.; Ambrosino, F.; Antonelli, L. A.; Aramo, C.; Arbet-Engels, A.; et al. (EDP Sciences, 2026)
Context. The Galactic magnetar SGR 1935+2154 has exhibited prolific high-energy (HE) bursting activity in recent years.
Aims. Investigating its potential tera-electronvolt counterpart could provide insights into the underlying mechanisms of magnetar emission and very high-energy (VHE) processes in extreme astrophysical environments. We aim to search for a possible tera-electronvolt counterpart to both its persistent and sub-second-scale burst emission.
Methods. We analysed over 25 hour of observations from the Large-Sized Telescope prototype (LST−1) of the Cherenkov Telescope Array Observatory (CTAO) during periods of HE activity from SGR 1935+2154 in 2021 and 2022 to search for persistent emission. For bursting emission, we selected and analysed nine 0.1 s time windows centred around known short X-ray bursts, targeting potential sub-second-scale tera-electronvolt counterparts in a low-photon-statistics regime.
Results. While no persistent or bursting emission was detected in our search, we establish upper limits for the tera-electronvolt emission of a short magnetar burst simultaneous to its soft gamma-ray flux. Specifically, for the brightest burst in our sample, the ratio between tera-electronvolt and X-ray flux is ≲10−3.
Conclusions. The non-detection of either persistent or bursting tera-electronvolt emission from SGR 1935+2154 suggests that if such components exist, they may occur under specific conditions not covered by our observations. This aligns with theoretical predictions of VHE components in magnetar-powered fast radio bursts and the detection of MeV–GeV emission in giant magnetar flares. These findings underscore the potential of magnetars, fast radio bursts, and other fast transients as promising candidates for future observations in the low-photon-statistics regime with Imaging Atmospheric Cherenkov Telescopes, particularly with the CTAO.